2019
DOI: 10.1155/2019/6514520
|View full text |Cite
|
Sign up to set email alerts
|

Sensors of Smart Devices in the Internet of Everything (IoE) Era: Big Opportunities and Massive Doubts

Abstract: Smart device industry allows developers and designers to embed different sensors, processors, and memories in small-size electronic devices. Sensors are added to enhance the usability of these devices and improve the quality of experience through data collection and analysis. However, with the era of big data and machine learning, sensors’ data may be processed by different techniques to infer various hidden information. The extracted information may be beneficial to device users, developers, and designers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 138 publications
0
43
0
Order By: Relevance
“…where P < The difference of (7) from (3) is that (7) uses forecasted message incoming rate. The equation from [9] is as follows:…”
Section: Producing Rate-based (Pr-b) As Scale-out Equation and Forecamentioning
confidence: 99%
See 1 more Smart Citation
“…where P < The difference of (7) from (3) is that (7) uses forecasted message incoming rate. The equation from [9] is as follows:…”
Section: Producing Rate-based (Pr-b) As Scale-out Equation and Forecamentioning
confidence: 99%
“…The scalability of processing and storage capacity is useful for a limited fraction of IoT scenarios. One of the most prominent examples is a smartwatch equipped with sensors measuring pulse, body temperature, altitude and various other characteristics of their owner [7]. These devices can be turned on and off frequently by their owners, on top of that these devices can change the location.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al suggested an interference synchronization mechanism to control spectrum sharing for Cognitive Radio (CR) networks, which is considered to be a powerful inference control strategy [8]. Yao Wang et al proposes a Cost and Connection Degree (CCB) algorithm that creates a new useful method to build a prototype to represent the overall utility of the process [14].…”
Section: Background Workmentioning
confidence: 99%
“…Regardless of the device it must always can sense elements of the environment they are calibrated to measure and then communication the data to then direct the implementation of the automated action, this communication also allows for machine learning. [143] Masoud, Jaradat, Manasrah and Jannoud [92] provide additional insight in their article, Sensors of Smart Devices in the Internet of Everything (IoE) Era: Big Opportunities and Massive Doubts, "a fridge with an embedded processor is not smart until it has the ability to communicate with people, other fridges, and supermarkets to order missing items. Moreover, it should select from different supermarkets to buy the items with price offers.…”
Section: Sensing In Smart Homesmentioning
confidence: 99%